MAIN DIRECTIONS OF EXPORTBOP PRODUCT DEVELOPMENT IN THE DIGITAL ECONOMY - Oltaev Sh.S (TADQIQOTLAR, 2026)
Abstract: This article examines the main directions of export production in the digital economy. At the same time, the article examines the problems associated with the use of international and national marketing. International marketing is analyzed as a  means  of  shaping  national  production  based  on  external  market  conditions, determining  its  specialization,  and  organizing,  managing  and  controlling  foreign economic and trade activities of companies. Methods for assessing the competitiveness of  export  products  are  analyzed.  The  impact  of  diversification,  modernization  and innovation factors affecting competitiveness is also analyzed, and their importance in increasing the country's export potential is revealed and explained.